KAJIAN EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PALA (Myristica Fragrans Houtt) - Bahrun, Sahrul; Ali Hasan, Asrul Dedy; Sofyan, Adnan; Abdurachman, Idris (Jurnal Pertanian Khairun, 2024)
Land evaluation is the process of assessing land potential for various alternative uses. Land suitability evaluation is very flexible, depending on the needs of the area's conditions to be evaluated. Improvement efforts carried out on land will provide an overview of optimal land use in order to increase land productivity. This research aims to determine the level of land suitability for nutmeg plants in Luari Village, North Tobelo District, North Halmahera Regency. This research method uses a purposive sampling method, a type of sampling technique commonly used in scientific research. The main goal of purposive sampling is to produce a sample that can logistically be considered representative of the population. Identification of soil properties in the field is carried out using boring identification techniques, ring samples, and representative profiles. Soil sampling techniques are carried out using a disturbed and undisturbed method to analyze the physical and chemical properties of soil in the laboratory. Research results the actual suitability of land for nutmeg (Myristica. Fragrans Houtt) is divided into marginally suitable class (S3) covering an area of 167.8 Ha at SPL 01, 02, 03, 04, 05 and unsuitable class (N) covering an area of 37.3 Ha at SPL 06, 07, 08, with limiting factors in the marginal suitability class (S3) in the form of soil depth, lack of P2O5, N-Total, and slope, while the limiting factor in unsuitable land suitability (N) is slope.